Integration of Digital Technologies in Physics Experiments: A Bibliometric Analysis - Wahyudi, Ismu; Rusdiana, Dadi; Samsudin, Achmad; Hasanah, Lilik; Kapici, Hasan Ozgur (Jurnal Pendidikan MIPA, 2024)
Digital technology plays an important role in physics experiments by increasing the accuracy of data collection, enabling complex simulations and conducting real-time analysis, which accelerates scientific discovery, and improve test accuracy. The purpose of this study is to provide an overview of the conduct of research on the integration of digital technologies into physics experiments. This study conduct a bibliometric analysis of the integration of digital technology into physics experiments from January 2014 to May 2024. Based on the keywords, only articles selected by SCOPUS in English were included, and using the PRISMA guidelines we obtained 344 articles for analysis. In this studies, sample articles from SCOPUS in *RIS formats are processed using the VOSviewer to facilitate visualization and trend detection. Our analysis revealed seven prominent trends, included e-learning, digital twin, numerical model, high energy physics, application specific integrate, analog electronic circuit, and tracking detectors. The inspection results show that there was no significant development, research on the integration of digital technology into physics experiments has not been seriously conducted from the point of view of future teachers and teacher education, and only a few countries have investigated it. Therefore, based on the results of this bibliometric analysis, it provides an overview and opportunities for further research.         Keywords: bibliometric, digital technology, physics experiments, VOSviewer.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp659-670